2004
DOI: 10.1074/jbc.m403937200
|View full text |Cite
|
Sign up to set email alerts
|

The Sphingosine-1-phosphate Receptors S1P1, S1P2, and S1P3 Function Coordinately during Embryonic Angiogenesis

Abstract: Sphingosine-1-phosphate (S1P) elicits diverse cellular responses through a family of G-protein-coupled receptors. We have shown previously that genetic disruption of the S1P 1 receptor, the most widely expressed of the family, results in embryonic lethality because of its key role within endothelial cells in regulating the coverage of blood vessels by vascular smooth muscle cells. To understand the physiologic functions of the two other widely expressed S1P receptors, we generated S1P 2 and S1P 3 null mice. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
335
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(353 citation statements)
references
References 40 publications
13
335
1
1
Order By: Relevance
“…underdeveloped limbs (Chae et al, 2004), and that a more severe limb abnormality is observed in S1p 1 S1p 2 double null mice (Kono et al, 2004). Chae et al (2004) have shown that S1P 1 signaling in the developing vasculature is essential for proper limb development.…”
Section: Potential Roles For Multiple Lpa/s1p Receptor Subtypes Durinmentioning
confidence: 99%
See 1 more Smart Citation
“…underdeveloped limbs (Chae et al, 2004), and that a more severe limb abnormality is observed in S1p 1 S1p 2 double null mice (Kono et al, 2004). Chae et al (2004) have shown that S1P 1 signaling in the developing vasculature is essential for proper limb development.…”
Section: Potential Roles For Multiple Lpa/s1p Receptor Subtypes Durinmentioning
confidence: 99%
“…Mice deficient in each of the LPA or S1P receptor genes (excluding Lpa 4 , Lpa 5 , and S1p 4 ) have been reported, and double-or triple-knockout mice have been produced for Lpa 1-3 and S1p 1-3 (Contos et al, 2000Kingsbury et al, 2003;Ye et al, 2005Ye et al, , 2008Liu et al, 2000;MacLennan et al, 2001MacLennan et al, , 2006Kono et al, 2004Kono et al, , 2007Cinamon et al, 2004;Jaillard et al, 2005;Herr et al, 2007;Means et al, 2007). However, none of the genetically modified mice reported so far appear to exhibit apparent deficiencies in the formation of somites, possibly because of functional compensation or redundancy among LPA/S1P receptor genes.…”
Section: Combinatorial Regulation Of Lysophospholipids Signaling By Mmentioning
confidence: 99%
“…Wide-spread hemorrhage and severe edema were observed at E13.5, and the mice could not survive beyond E14.5 [6]. Although both S1P 2 -and S1P 3 -null mice developed normally vascular systems, S1P 1 S1P 2 double knockout mice and S1P 1 S1P 2 S1P 3 triple knockout mice exhibited more severe vascular defects than those of the S1P 1 single knockout mice [23]. About half of the triple null mice exhibited bleeding at E10.5, and most of those died at E11.5.…”
Section: Discussionmentioning
confidence: 98%
“…Hearts from heparinized adult C57Bl/6 or S1P 3-null mice (28) were isolated under isoflurane anesthesia in accordance with protocols approved by the Institutional Animal Care and Use Committee at UCSD. Guidelines for the Care and Use of Laboratory Animals (copyright 1996) were adhered to.…”
Section: Isolation Of Ventricular Myocytesmentioning
confidence: 99%